Rheological study of Jabuticaba pulp with different concentrations of arabic gum (Research, Society and Development, 2020)
This study aimed to compare rheological analyzes in the function of adding an encapsulated agent that can be found in Jabuticaba. The rheological study was performed according to the concentration of gum arabic (0, 5, 10 and 15%) and the rheological models of Bingham, Mizrahi-Berk, Casson, Herschel-Bulkley and Ostwald-de-Waelle (Law of Power) adjusted to the experimental data. Herschel-Bulkley and Mizrahi-Berk rheological models presented the best adjustments for all formulations with coefficients of determination (R2) greater than 0.99 and chi-square function less than 0.12. It was observed that the consistency index increased with the addition of gum arabic to the Herschel-Bulkley and Ostwald-de-Waele models, indicating that they became more consistent and the viscosity decreased with increasing strain rate of the fluid. Therefore, the rheological study indicated that the pulp and its formulations, with the addition of the encapsulating agent, presented non-Newtonian fluid behavior, in the specific case of a pseudoplastic.